Rehabilitation interventions delivered via telehealth to support self-management of rheumatic and musculoskeletal diseases: A scoping review protocol. - Rosemarie Barnett; Nuzhat Shakaib; Thomas A Ingram; Simon Jones; Raj Sengupta; Peter C Rouse (PLoS ONE)
Background Telerehabilitation is a term to describe rehabilitation services delivered via information and communication technology. Such services are an increasingly important component for the management of rheumatic and musculoskeletal diseases (RMDs). Telerehabilitation has the potential to expand the long-term self-management options for individuals with RMDs, improve symptoms, and relieve pressures on health care services. Yet, little is known about the variety of interventions implemented, and how they are being evaluated. Thus, this scoping review aims to identify and describe existing rehabilitation interventions delivered via telehealth for RMDs. Specifically, we aim to identify and summarize the key components of rehabilitation, the technology used, the level of health care professional interaction, and how the effectiveness of interventions is evaluated. Methods We will conduct this review following the latest JBI scoping review methodology and the PRISMA guidelines for Scoping Reviews (PRISMA-ScR). The 'Population-Concept-Context (PCC)' framework will be used, whereby the 'Population' is RMDs (≥18 years); the 'Concept' is rehabilitation; and the 'Context' is telehealth. Developed in collaboration with a subject Librarian, refined PCC key terms will be utilized to search (from 2011-2021) three electronic databases (i.e., Embase, Scopus, Web of Science) for articles published in English. Search results will be exported to the citation management software (EndNote), duplicates removed, and eligibility criteria applied to title/abstract and full-text review. Relevant information pertaining to the PCC framework will be extracted. Data will be summarized qualitatively, and if appropriate, quantitatively via frequency counts of the components comprising the 'Concept' and 'Context' categories of the PCC framework. Discussion Findings from the proposed scoping review will identify how telehealth is currently used in the delivery of rehabilitation interventions for RMDs. The findings will develop our understanding of such interventions and provide a platform from which to inform future research directions.